Pengembangan Aplikasi Inventaris Barang Berbasis Web Menggunakan Metode Prototype dengan Pengujian PIECES: Pengembangan Aplikasi Inventaris Barang Berbasis Web Menggunakan Metode Prototype dengan Pengujian PIECES - Risdayati, Sunni; Fajrian Noor , Muhammad; Khotib, Muhammad (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
This research was conducted to address the problem of manual inventory recording at MAN 3 Banjar,which is inefficient. The proposed solution is the development of a web-based inventory applicationusing the prototype method, which allows users to be directly involved in the development process.To evaluate the system’s quality, testing was conducted using the PIECES framework coveringperformance, information, economy, control, efficiency, and service. The results show that theprevious manual system had several problems, such as slow recording, risk of data loss, and limitedinformation access. The developed application provides features for item recording, tracking incomingand outgoing goods, and report generation. Based on black box testing and PIECES questionnaires,the application received positive responses from users with satisfaction levels ranging from satisfiedto very satisfied. Therefore, this application is expected to be an effective solution for improving schoolinventory management.